Epigenetics as an interdiscipline? Promises and fallacies of a biosocial research agenda. (March 2020) - Dubois, Michel; Louvel, Séverine; Rial-Sebbag, Emmanuelle
Following the spectacular rise of epigenetics since the early 2000s, an increasing number of social scientists have called for it to be recognized as an 'interdiscipline', at the crossroads of the life sciences and the social sciences. The aim of this special issue is to advance our knowledge of epigenetics and to address three main issues: the epistemological, conceptual and empirical transformations induced by epigenetic research, the public dissemination of epigenetic knowledge, and finally the normative and sociopolitical implications of epigenetics.